Atraumatic restorative treatment compared to the Hall Technique for occluso-proximal carious lesions in primary molars; 36-month follow-up of a randomised control trial in a school setting - Mariana Pinheiro Araujo; Nicola Patricia Innes; Clarissa Calil Bonifácio; Daniela Hesse; Isabel Cristina Olegário; Fausto Medeiros Mendes; Daniela Prócida Raggio (BMC Oral Health, 2020)
Abstract Background Atraumatic Restorative Treatment (ART) and the Hall Technique (HT) are both minimally invasive, non-aerosol generating procedures (non-AGPs). They seem to have never been directly compared, nor has the HT been studied in a non-clinical setting. This study compared the HT and ART restorations placed in a school setting after 36 months. Methods Children (5–10 yo) who had a primary molar with a dentinal occluso-proximal, cavitated carious lesion were allocated to the ART (selective removal) or HT arms. Primary outcome: restoration survival over 36-months (using Kaplan–Meier survival analysis, log rank test, and Cox regression). Secondary outcomes: (1) occlusal vertical dimension (OVD) (1, 2, 3, 4 weeks) and (2) child self-reported discomfort; (3) treatment acceptability (immediately following interventions); (4) Child Oral Health Related Quality of Life (OHRQoL), before treatment and after 6 months and (5) a post hoc analysis of time to tooth exfoliation (1, 6, 12, 18, 24, 30, 36 months). Results One-hundred and thirty-one children (ART = 65; HT = 66) were included (mean age = 8.1 ± 1.2). At 36 months, 112 (85.5%) children were followed-up. Primary outcome: restoration survival rates ART = 32.7% (SE = 0.08; 95% CI 0.17–0.47); HT = 93.4% (0.05; 0.72–0.99), p < 0.001; Secondary outcomes: (1) OVD returned to pre-treatment state within 4 weeks; (2) treatment discomfort was higher for the HT (p = 0.018); (3) over 70% of children and parents showed a high acceptability for treatments, with crown aesthetics being a concern for around 23% of parents; (4) Child OHRQoL improved after 6 months; and (5) teeth treated with the HT exfoliated earlier than those in the ART group (p = 0.007). Conclusions Both ART and the HT were acceptable to child participants and their parents and all parents thought both restorations protected their child’s tooth. However, the crown appearance concerned almost a quarter of parents in the HT arm. Children experienced less discomfort in the ART group. Although both treatments can be performed in a non-clinical setting and have the advantage of being non-aerosol generating procedures (non-AGPs), the HT had almost three times higher survival rates (93.4%) for restoring primary molar occluso-proximal cavities compared to ART (32.7%). Trial registration This trial was registered in ClinicalTrials.gov (NCT02569047), 5th October 2015. https://clinicaltrials.gov/ct2/show/study/NCT02569047?cond=Hall+Technique+Atraumatic+Rest orative+Treatment&draw=2&rank=2.